2015
DOI: 10.4193/rhino14.086
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of DNA methylation in the pathogenesis of chronic rhinosinusitis with nasal polyps

Abstract: Background: DNA methylation has been implicated in the pathogenesis of allergy and atopy. This study aimed to identify whether DNA methylation also plays an important role in the pathogenesis of nasal polyps (NP). Methodology: NP tissues were obtained from 32 patients with chronic rhinosinusitis with bilateral NP. Biopsies of inferior turbinate mucosa (ITM) were taken from 18 patients who underwent rhinoseptoplasty (control group). The methylated genes, which were detected by DNA methylation microarray, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The identification of epigenetic changes and effects on gene silencing or expression opens up the potential of novel targeted drugs such as DNA methyltransferase inhibitors and histone deacetylase (HDAC) inhibitors. 21,22,46 In accordance with prior CRS epigenetic studies, 18,19,21,[25][26][27][30][31][32]47 we compared ethmoidal tissue from CRS subjects with IT from controls. We noted both hypermethylation and hypomethylation differences in CRS tissue compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of epigenetic changes and effects on gene silencing or expression opens up the potential of novel targeted drugs such as DNA methyltransferase inhibitors and histone deacetylase (HDAC) inhibitors. 21,22,46 In accordance with prior CRS epigenetic studies, 18,19,21,[25][26][27][30][31][32]47 we compared ethmoidal tissue from CRS subjects with IT from controls. We noted both hypermethylation and hypomethylation differences in CRS tissue compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…A scant number of studies in asthma have investigated single-cell DNA methylation. However, all genome wide methylation studies in CRS have used bulk tissue 17,32,47 and other DNA methylation studies in CRS have also used it. 23 We did not replicate or validate our current findings.…”
Section: Limitations and Strengths Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that changes in gene expression caused by methylation can lead to cellular overgrowth and widespread inflammation in the respiratory tract [ 22 ]. In the nasal mucosal tissues of CRS patients, 2848 genes showed differential methylation, which was mainly functionally characterized as being associated with inflammation [ 23 ]. In a report related to DNA methylation associated with CRS, differences in DNA methylation were observed between the eosinophilic CRSwNP and non-eosinophilic CRSwNP, resulting in different pathological characteristics [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study has reported higher methylation levels of 198 genes in the promoter regions in NPs, compared to those in inferior turbinate mucosa samples, and the top four most hypermethylated genes are collagen type XVIII alpha 1 chain (COL18A1), E1A-binding protein p300 (EP300), alpha subunit of the GTP-binding stimulatory protein (GNAS) and Smad ubiquitination regulatory factor 1 (SMURF1). COL18A1, with a higher methylation frequency than the others, has inspired the exploration into the mechanisms of CRSwNP ( Zheng et al, 2015 ). Another report has also shown the DNA methylation levels at all CpG sites are higher in NPs compared with those in inferior turbinate mucosa, with tissue-type plasminogen activator (t-PA, gene name PLAT) as the most obvious ( Kidoguchi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%